Combination chrome and mangrove (Rhizophora mucronata) bark crude extract on Epinephelus sp. leather quality. Issue 1 (March 2021) - Dewi, G S P; Saputra, E; Abdillah, A A
Abstract: Almost all tanning leather industry used chrome sulphate mineral because it has a high tannic power and produce tanned leather with good quality. However. as much as 25% chrome in tanning is wasted as liquid waste. Chrome as waste product from tanning process is categorized as dangerous waste which is toxic to the environment. The aim of this study was to determine the effect of combination chrome and mangrove bark crude extract on tanned Epinephelus sp. skin. The results showed that the best grouper skin was tanned on 8% tanner extract. which was demonstrated a tensile strength value by 228.91 kgf/cm 2, tear strength by 23.43 kgf/cm, elongation by 24.03%, and shrinkage temperature by 55.23° C. This studied promised application of mangrove extract could replace chrome as tanned agent for greenly method.